The Role of Organizational Commitment in Mediating Core Capabilities on Employee Performance in Multifinance Companies in Serang City - Nindya Jeni Prastika; Furtasan Ali Yusuf; Uli Wildan Nuryanto (LPPPIPublishing, 2023)
The purpose of this research is to analyze the role of organizational commitment in mediating core capabilities on employee performance in Multifinance Companies in Serang City. The research method used is a quantitative method. Population in this study are 209 employees of Multifinance Companies in Serang City. Sample used is 105 people. This study uses inductive data analysis technique. The results of this study show that core capabilities has a significant effect on organizational commitment in Multifinance Companies in Serang City. Core capabilities has a significant effect on employee performance in Multifinance Companies in Serang City. Organizational commitment has a significant effect on employee performance in Multifinance Companies in Serang City. There is a significant effect between core capabilities on employee performance through organizational commitment.